2009
DOI: 10.1002/bin.293
|View full text |Cite
|
Sign up to set email alerts
|

The effect of behavioral skills training with general‐case training on staff chaining of child vocalizations within natural language paradigm

Abstract: This study used behavioral skills training (BST) and general-case training (GCT) in which the experimenter simulated child performance to teach three staff to conduct NLP and response chaining to increase three-link vocal chains in three children with autism. Staff increased their correct NLP performance during post-training in comparison to baseline. Two of three children emitted more vocal chains following training. This study demonstrated that BST and GCT were effective in training NLP and response chaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 13 publications
(15 reference statements)
4
52
0
Order By: Relevance
“…In particular, the tactic of general case training seems likely to produce changes in staff behavior that extend to untrained clients, tasks, and settings (e.g., Ducharme, Williams, Cummings, Murray, & Spencer, 2001;Ducharme & Feldman, 1992;Seiverling et al, 2010;Ward-Horner & Sturmey, 2008). Although coverage of the full range of strategies to enhance generalization is beyond the scope of the current review, professional trainers who examine this literature are sure to find additional means to bolster their work with teachers and staff.…”
Section: Practical Considerationsmentioning
confidence: 92%
“…In particular, the tactic of general case training seems likely to produce changes in staff behavior that extend to untrained clients, tasks, and settings (e.g., Ducharme, Williams, Cummings, Murray, & Spencer, 2001;Ducharme & Feldman, 1992;Seiverling et al, 2010;Ward-Horner & Sturmey, 2008). Although coverage of the full range of strategies to enhance generalization is beyond the scope of the current review, professional trainers who examine this literature are sure to find additional means to bolster their work with teachers and staff.…”
Section: Practical Considerationsmentioning
confidence: 92%
“…Of these studies, six studies evaluated the effects of staff training on staff members' fidelity of implementation of PRT or NLP (Gianoumis et al 2012;Huskens et al 2012;Robinson 2011;Seiverling et al 2010;Suhrheinrich 2011;Suhrheinrich et al 2007). Additionally, Gianoumis et al (2012) evaluated the effect of staff training on staff members' ability to conduct a stimulus preference assessment.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Video feedback was used in four studies and in vivo feedback in 18 studies. Several studies incorporated additional instructional strategies, such as small group discussions , assessments (e.g., Seiverling et al 2010), picture prompts (e.g., Harper et al 2008) and reinforcement (Kuhn et al 2008). Stahmer and Gist (2001) investigated the addition of a parent information support group to PRT parent training.…”
Section: Intervention Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned prompting strategies may need to be modified to accommodate lengthier intraverbal responses, such as retelling of short stories. There are research studies that have demonstrated the successful use of chaining in combination with echoic training to increase the complexity of vocal responses (Seiverling et al 2010;Tarbox et al 2009). Thus, it is possible that echoic and visual prompting methods may be combined with chaining to teach complex intraverbal responses like storytelling to children with autism.…”
mentioning
confidence: 99%